2014
DOI: 10.1016/j.virol.2014.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis of viromes of dromedary camel fecal samples reveals large number and high diversity of circoviruses and picobirnaviruses

Abstract: The recent discovery of Middle East Respiratory Coronavirus and another novel dromedary camel coronavirus UAE-HKU23 in dromedaries has boosted interest in search of novel viruses in dromedaries. In this study, fecal samples of 203 dromedaries in Dubai were pooled and deep sequenced. Among the 7330 assembled viral contigs, 1970 were assigned to mammalian viruses. The largest groups of these contigs matched to Picobirnaviridae, Circoviridae, Picornaviridae, Parvoviridae, Astroviridae and Hepeviridae. Many of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 50 publications
4
44
1
Order By: Relevance
“…The first human-feces-associated PeCV was reported in a patient during an outbreak of acute gastroenteritis in the Netherlands (VS6600022) [27]. Other related genomes were found in feces from asymptomatic mammals [4, 24, 30]. Here, we also report PeCV genomes in human feces from Peru, Nicaragua and Chile, while diarrhea samples from Brazil and Venezuela were PCR negative.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The first human-feces-associated PeCV was reported in a patient during an outbreak of acute gastroenteritis in the Netherlands (VS6600022) [27]. Other related genomes were found in feces from asymptomatic mammals [4, 24, 30]. Here, we also report PeCV genomes in human feces from Peru, Nicaragua and Chile, while diarrhea samples from Brazil and Venezuela were PCR negative.…”
Section: Discussionmentioning
confidence: 51%
“…For cycloviruses, the cellular hosts remain unknown but may include mammals and/or insects cells, or conceivably, originate from consumed animals or plants. Another distinct clade of viruses with CRESS-DNA genomes was also described in the feces of chimpanzees and other mammals, including pigs, rats [1, 35, 10, 18, 21, 22, 25, 26, 30], and recently humans [14], whose cellular hosts are also unknown. Yet another clade of CRESS-DNA genomes whose cellular hosts are not known was reported in the feces of pigs, seals, dromedaries and humans [4, 24, 27, 30].…”
Section: Introductionmentioning
confidence: 99%
“…The same group of authors identified that picobirnaviruses from different foxes were not identical. The divergence of picobirnaviruses within species has been proved previously in humans [27], pigs [28] and Dromedary camels [29].…”
Section: Discussionmentioning
confidence: 69%
“…Densoviruses are also frequently detected in mosquitos, showing variable degrees of pathogenicity [3, 23]. Densovirus sequences are also reported in feces of rodents [19], bats [8, 14], and camels [30]; likely reflecting viruses in their diets.…”
Section: The Studymentioning
confidence: 99%